Fear as a barrier: early desertion from a public scholarship program in Peru «Beca 18» - Aramburú, Carlos E. (2019)
This article explores the reasons why low-income students, who are supported by a public scholarship program called “Beca 18”, reject this support or leave their studies during the first year of studies. Results are based on two methods: a quantitative model that compares personal and family characteristics among deserters and non-deserters, and a qualitative approach based on in-depth interviews with deserters in order to inquire about the reasons for not accepting the scholarship or early withdrawal. This article prioritizes the qualitative approach because the quantitative does not show significant differences between the two groups. The evidence indicates that the main reasons that explain the early drop-out or non-acceptance of Beca 18 are the affective factors and the lack of social integration into the new environment.